ALAT SENSOR PARKING BERBASIS IOT - Aldo Nurfahmi, Muhammad; Ramadhan Hydayatullah, Syarif; Yudhi, Yudhi; Badriyah, Badriyah (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The development of Internet of Things (IoT) technology has opened new opportunities in creating efficient and modern parking systems. This study aims to design and develop an automatic parking sensor device based on IoT that can detect the presence of vehicles and display parking availability data in real-time via an application. The system utilizes ultrasonic sensors to detect vehicles, an ESP32 microcontroller as the control center, and an IoT platform to transmit data to the user’s device. The test results show that the system operates with more than 95% accuracy and provides fast and precise parking slot availability information. In conclusion, this device is effective in assisting users to find available parking spaces and has the potential for further development in smart parking systems.